Upaya Guru Katolik dalam Meningkatkan Nilai– Nilai Kerohanian Siswa di Sekolah Dasar Inpres Lewobele Kecamatan Adonara Tengah Kabupaten Flores Timur - Agustina Deran Payon; Benedikta Boleng; Chatarina Novianti (Departement of Mathematics Education, 2023)
The aim is to find out the Catholic Teacher's Efforts in Improving Students' Spiritual Values ​​at SD Inpres Lewobele. The approach of this research uses a qualitative approach. Data collection was carried out using interview techniques, observation and documentation. The data collected through this technique was then analyzed descriptively qualitatively. The results of this study indicate that the spiritual values ​​of SD Inpres Lewobele Elementary School students are still found by students who have not good spiritual values, but there are also students who already have good spiritual values. The Catholic teacher's efforts to increase the spiritual value of students have been carried out by the Catholic teacher, but the role of the Catholic teacher as a whole is still needed so that increasing the spiritual value is well realized.